Fertilizing Trees - Carlson, Dennis W. (My University, 2001)
Trees planted or growing in modified urban soils can benefit from added fertilizer when soil is moved during construction of the home.
L707_2001-05
Keywords: L707; Environment and Natural Resources; Lawn and Garden; Forestry; L